ANALISIS PENGARUH SIZE, CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSETS (ROA), NON PERFORMING LOAN (NPL), DAN INFLASI TERHADAP LOAN TO DEPOSIT RATIO (LDR) - Ramadhani, Aulia Nazala; Indriani, Astiwi (Diponegoro Journal of Management, 2016)
This research was conducted to examine the influence of the size, Capital Adequacy Ratio (CAR), Return On Assets (ROA), Non Performing Loan (NPL), and inflation toward Loan to Deposit Ratio (ROA).The  population  of  this  research  is  the  conventional  commercial  bank  listed  on  the Indonesia Stock Exchange period 2010 through 2014. Purposive sampling method were used as samples determining method and 21 banks selected as the sample of this research. Analysis Method with multilinier regression of ordinary least square and hypotheses test used t-statistic and F-statistic at level significance 5%, a classic assumption examination which consist of normality test, multicolinearity test, heteroscedasticity test and autocorrelation test is also being done to test the hypothese.The results of the research simultantly using F test, showed that size, Capital Adequacy Ratio (CAR),  Return On Assets  (ROA),  Non  Performing  Loan  (NPL),  and  inflation  variables influence significantly toward Loan to Deposit Ratio (LDR). Partially varibles using t test, showed size is not significant negative influence on the LDR with a significance level of 0,705 > 0,050, CAR is not significant positive influence on the LDR with a significance level of 0,801 > 0,050, ROA is not significant positive influence on the LDR with a significance level of 0,973 > 0,050, NPL is significance negative influence on the LDR with a significance level of 0,017 < 0,050, and inflation is significant positive influence on the LDR with a significance level of 0,009 < 0,050. The coefficient determinant (r square) is 0,238 which means 23,8% LDR variation explained by size, CAR, ROA, NPL, and inflation, whereas  76,2% explained by another variables which was not to be entered in the research model.